1987
DOI: 10.1111/j.1943-278x.1987.tb00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Suicide and Wife Abuse: A Cross‐Cultural Perspective

Abstract: Data from a number of societies, including North America, indicate that wife abuse may be one of the most significant precipitants of female suicide. Anthropological analysis indicates that in some societies female suicide is a culturally recognized behavior that enables the weak to influence the strong and/or take revenge on those who oppress them. Case studies from West New Britain Province in Papua New Guinea and comparisons with data from other societies suggest that if a woman's support group does not def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
3

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 9 publications
0
51
0
3
Order By: Relevance
“…[19][20][21][22][23][24] Similarly, in our study, women with IPV exposure used more alcohol (26.3% alcohol dependence, 10.5% alcohol abuse), had a trend towards …”
Section: Discussionmentioning
confidence: 92%
“…[19][20][21][22][23][24] Similarly, in our study, women with IPV exposure used more alcohol (26.3% alcohol dependence, 10.5% alcohol abuse), had a trend towards …”
Section: Discussionmentioning
confidence: 92%
“…Large community studies found that severe partner assault increased rates of depressed mood by four times and rates of attempted suicide by five (Straus and Gelles, 1990) and that physical assault by partners was associated with higher depression scores in victims (Mullen et al, 1988;Ratner, 1993;Zlotnick et al, 1998). Ethnographic studies in the Americas (Jenkins, 1991) and Oceania (Counts, 1987;Counts 1990aCounts , 1990b link wife beating to depressed mood, suicide, and culture-specific mental illness. Regarding ethnic Chinese, being beaten by a spouse was the third most common reason given for attempted suicide by young rural women in China, a group known to have particularly high rates of completed suicide (Pearson et al, 2002).…”
mentioning
confidence: 94%
“…All nonAboriginal, female, sole parents who responded to the door-step invitation or notes left at their houses yielded a further 13 -and two refusals. The final non-Aboriginal sample was therefore 45.…”
Section: Methodology and Samplingmentioning
confidence: 99%